ANALISA KUAT TEKAN BETON K 300 DENGAN PENAMBAHAN SEMEN MORTAR UTAMA TYPE 420 - Asrullah, Asrullah (Jurnal Teknik Sipil, 2019)
Mortar Utama Cement has various types appropriate to its usage, and this research uses an additive of Mortar Utama cement Type 420. This research is conducted at laboratory scale in the form of experiment for the purpose to know the value of concrete strength by using Mortar Utama Cement Type 420 as concrete mixing additive. The concrete mixing method being used is SNI 03-2834-2000. The concrete quality being used is K 300 with test item 15 x 15 x 15 cm in size by adding Mortar Utama Cement for 5%, 10%, 15% and 20% of cement weight. The strength is tested on the 3rd, 14th, 21stand 28th days of concrete making. According to the test result, we can conclude that the highest strength of concrete K 300 with 5% addition is 325.32 kg/cm2. Adding Mortar Utama cement type 420 is able to influence the strength of concrete with simple linear regression model for K 300 : Y = -3.061x + 328.3 with R2 = 0.731.